การทำนายพฤติกรรมแยกขยะพลาสติกในครัวเรือนด้วยทฤษฎีพฤติกรรมตามแผนและการพิจารณาถึงผลลัพธ์ในอนาคต - พีรยา พูลหิรัญ (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
Household plastic waste separation behavior is one of the significant ways to solve the long-term plastic problem when plastic packaging eradication seems impossible. This research aimed to investigate factors of the Theory of Planned Behavior (TPB) and Consideration of Future Consequences (CFC) predicting household waste separation behavior focusing on 3 types of single-use plastic: plastic bags, plastic food bags, and plastic food containers. Participants (n = 126), age 18 and over who lived in Bangkok for at least 1 year, answered the online questionnaires then reported their household waste separation behavior 2 weeks later. According the results, perceived behavioral control affected behavior directly and indirectly through the intention while subjective norm only had an indirect effect on behavior. Attitude toward behavior and consideration of future consequences did not affect behavior via intention. And perceived behavioral control did not moderate the effects of attitude and subjective norm on intention. Perceived behavioral control had the most important impact on behavior. Participants believed that they could perform behaviors more easily if there were some space or separated trash cans for types of waste. Perceiving the advantages of behavior also encouraged them to sort plastic waste.